The Coed Conundrum: Unraveling Gender Identities in Private Schools of Muzaffarabad - Ayesha Habib Khan; Noor.ul. Ain Gillani; Urooj Azmat (Journal of Peace, Development and Communication, 2024)
This article explores the dynamics of gender identity construction in educational settings, specifically focusing on private schools in Muzaffarabad, Pakistan. It provides a comprehensive analysis of how gender identity constructions are shaped within the school environment, considering the social, political, and economic contexts that influence these processes. Through qualitative analysis and data collected from teachers and students, the study examines how classroom dynamics, curriculum content, and teaching approaches contribute to the shaping of gender identities. Findings reveal diverse perspectives among teachers, with varying views on gender roles and education. Some teachers advocate for gender-neutral approaches, encouraging all students to excel in their chosen fields, while others emphasize traditional gender roles, linking education to societal needs and domestic responsibilities. Student responses reflect a range of experiences, from challenging gender stereotypes to navigating societal expectations. Significantly, the study observes a positive shift in school perspectives compared to the literature being reviewed, with teachers and schools working towards a more neutral approach in the construction of gender identity. The study calls for further studies to explore the impact of inclusive and empowering educational practices on students’ self-perceptions, aspirations, and career choices, with a focus on fostering gender equity and challenging stereotypes.